TINDAK PIDANA PENYALAHGUNAAN PENGGUNAAN KARTU KREDIT DAN UPAYA PENANGGULANGAN PENYALAHGUNAAN KARTU KREDIT - Andin Rusmini (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
AbstractCredit card is one of tool for simply payment, and its giving efficient and more value for customer. It is also completing retail transaction that publish as a payment tool that used in some transaction. Criminal acts of credit cards abuse is an act committed by some individuals or groups which missues credit cards. Utilization of this acts is often haven already becoming more frequent, either conducted by the owner of the credit card or by hackers who using chips from customer of credit card. In order to reduce criminal act that using credit cards at banks, the goverment published some regulation in the form of Regulation Indonesian Bank and Indonesian Bank Circular Letter, this regulation obligated banks to implement management risk in the activity of internet banking. This regulation is implement principle of know your customer / Know Your Customer Principles (KYCP) and to secured technology information system in activity of payment by using Credit Card and implemented information transparency related to Bank products and the utilizations of Customer Personal Data.Keywords: Credit Card, Credit Card Crime, Effort of Prevention of Credit Card Abuse.